Relative Contribution of PIN-Containing Secretory Vesicles and Plasma Membrane PINs to the Directed Auxin Transport: Theoretical Estimation - Hille, Sander; Akhmanova, Maria; Glanc, Matouš; Johnson, Alexander; Friml, Jiří (International journal of molecular sciences, 2018)
The intercellular transport of auxin is driven by PIN-formed (PIN) auxin efflux carriers. PINs are localized at the plasma membrane (PM) and on constitutively recycling endomembrane vesicles. Therefore, PINs can mediate auxin transport either by direct translocation across the PM or by pumping auxin into secretory vesicles (SVs), leading to its secretory release upon fusion with the PM. Which of these two mechanisms dominates is a matter of debate. Here, we addressed the issue with a mathematical modeling approach. We demonstrate that the efficiency of secretory transport depends on SV size, half-life of PINs on the PM, pH, exocytosis frequency and PIN density. 3D structured illumination microscopy (SIM) was used to determine PIN density on the PM. Combining this data with published values of the other parameters, we show that the transport activity of PINs in SVs would have to be at least 1000× greater than on the PM in order to produce a comparable macroscopic auxin transport. If both transport mechanisms operated simultaneously and PINs were equally active on SVs and PM, the contribution of secretion to the total auxin flux would be negligible. In conclusion, while secretory vesicle-mediated transport of auxin is an intriguing and theoretically possible model, it is unlikely to be a major mechanism of auxin transport in planta.
Keywords: 3D-SIM microscopy; Arabidopsis; sekreční vezikuly; mathematical modeling; Cell Membrane Permeability; zelené fluorescenční proteiny; Models, Biological; kyseliny indoloctové; secretion; Indoleacetic Acids; biologické modely; proteiny huseníčku; Secretory Vesicles; PIN transporters; Arabidopsis Proteins; Green Fluorescent Proteins; Endocytosis; Biological Transport; polar auxin transport; auxin; biologický transport; permeabilita buněčné membrány; endocytóza